Performance of the novel ANTWERP score in predicting heart function improvement after atrial fibrillation ablation in Asian patients with heart failure - Lo‐Chieh Ling; Ting‐Yung Chang; Yenn‐Jiang Lin; Chin‐Yu Lin; Shih‐Lin Chang; Li‐Wei Lo; Yu‐Feng Hu; Fa‐Po Chung; Shih‐Ann Chen (Journal of Arrhythmia)
Abstract Background Previous research has demonstrated that atrial fibrillation (AF) ablation improves heart function variably among patients. We proposed that the ANTWERP score, which was validated in a European group of patients with low left ventricular ejection fraction (LVEF) who had AF ablation, would be valid in an Asian group as well. The purpose of the study is to examine how well a new scoring system (the ANTWERP score) can predict heart function improvement after atrial fibrillation ablation in Asian patients with heart failure. Methods A retrospective review was conducted on patients (n = 84) undergoing AF ablation between January 2019 and June 2022. Initial diagnoses for impaired LV systolic function were confirmed by echocardiography. Patients meeting the “2021 Universal Definition of HF” criteria for LVEF recovery were classified as “responders.” Results Similarities were observed between responders and nonresponders regarding comorbidities, AF type, and LVEF, except for the left ventricular internal diameter in diastole. A higher percentage of responders had an ANTWERP score ≤2 (87.8%) compared to those with a score >2 (55.6%). LVEF improvement was notably higher in the former group (+14.8% vs. +9.4%, p = .043). Atrial reverse remodeling and recurrent atrial arrhythmia rates were similar across groups. Conclusion The conclusion of the study was that the ANTWERP score effectively predicted LVEF improvement after atrial fibrillation ablation in the Asian population and that this scoring system could be used to guide clinical decisions and prognosis prediction.